Scalable Production of Lipid Nanoparticles Containing Amphotericin B - Kulkarni, Jayesh A (Langmuir : the ACS journal of surfaces and colloids, 2021)
Lipid-based formulations have been developed to improve stability profiles, tolerability, and toxicity profiles of small molecule drugs. However, manufacture of such formulations involving lipophilic compounds can be labor-intensive and difficult to scale because of solubility and solvent compatibility issues. We have developed a rapid and scalable approach using rapid-mixing techniques to generate homogeneous lipid nanoparticle (LNP) formulations of siRNA, triglycerides, and hydrophilic weak-base drugs. Here, we used this approach to entrap a hydrophobic small molecule, Amphotericin B (AmpB), a hydrophobic drug not soluble in ethanol. The three prototypes presented in this study were derived from LNP-siRNA systems, triglyceride nanoparticles, and liposomal systems. Cryogenic transmission electron microscopy (cryo-TEM) revealed that all three LNP-AmpB formulations retain structural characteristics of the parent (AmpB-free) LNPs, with particles remaining stable for at least 1 month. All formulations showed similar in vitro toxicity profiles in comparison to AmBisome. Importantly, the formulations have a 2.5-fold improved IC50 for fungal growth inhibition as compared to AmBisome in in vitro efficacy studies. These results demonstrate that the rapid-mixing technology combined with dimethyl sulfoxide (DMSO) for drugs insoluble in other organic solvents can be a powerful manufacturing method for the generation of stable LNP drug formulations